Radiological Assessment of the Indian Children with Congenital Sensorineural Hearing Loss. (14th July 2014) - Agarwal, Sangeet Kumar; Singh, Satinder; Ghuman, Samarjit Singh; Sharma, Shalabh; Lahiri, Asish Kr.
Abstract : Introduction . Congenital sensorineural hearing loss is one of the most common birth defects with incidence of approximately 1 : 1000 live births. Imaging of cases of congenital sensorineural hearing loss is frequently performed in an attempt to determine the underlying pathology. There is a paucity of literature from India and for this reason we decided to conduct this study in Indian context to evaluate the various cochleovestibular bony and nerve anomalies by HRCT scan of temporal bone and MRI with 3D scan of inner ear in a tertiary care centre. Material and Methods . A total of 280 children with congenital deafness (158 males and 122 females), between January 2002 to June 2013 were included in the study and they were assessed radiologically by HRCT scan of temporal bone and MRI with 3D scan of inner ear. Results . In the present study we found various congenital anomalies of bony labyrinth and vestibulocochlear nerve. Out of 560 inner ears we found 78 anomalous inner ears. Out of these 78 inner ears 57 (73%) had cochlear anomaly, 68 (87.1%) had anomalous vestibule, 44 (56.4%) had abnormal vestibular aqueduct, 24 (30.7%) had anomalous IAC, and 23 (29.4%) had abnormal cochleovestibular nerves. Conclusion . In present study, we found lower incidences of congenital anomalies comparative to existing literature.